DISIPLIN ROHANI BAGI MAHASISWA STT EBENHAEZER: PRESPEKTIF DALAM PERJANJIAN LAMA - Jeane Paath; Wince Ziliwu (Sekolah Tinggi Teologi Arastamar Bengkulu, 2023)
The purpose of this research is to find God's truth about spiritual discipline in the Old Testament as a basis for theology students in completing their study assignments at STT Ebenhaezer Tanjung Enim. This is motivated by the lack of student understanding of spiritual discipline, especially students who have received disciplinary sanctions from institutions. In order to solve the above problems, research was carried out using descriptive-bibliological methods especially in the Old Testament. The result is the basis of spiritual discipline, namely the law, God's revelation and God's promises. The principle of spiritual discipline is to be carried out continuously, in the form of orders and various regulations, educating in truth and proclaiming justice. The purpose of spiritual discipline is for God's people to experience repentance, improve spiritual quality and bring God's people to true worship. The pattern of spiritual discipline is through the traditions of God's people, teaching, warnings and punishment.